Dynamics of transformation of economic activity of the population in the Republic of Tuva (2016–2022) - Ryazantsev, Sergey V.; Rostovskaya, Tamara K.; Vasilieva, Ekaterina N.; Süleymanlý, Ebulfez (The New Research of Tuva, 2024)
The article analyzes the dynamics of economic activity transformation among the population of the Republic of Tuva from 2016 to 2022 and systematizes data on the institutional conditions affecting economic activity in the region. Economic activity in this context is understood as the dynamics in the number of self-employed individuals, statistics on entrepreneurship development, and the distribution of employment across different economic sectors. It was found that, prior to 2021, positive dynamics in economic activity were either absent or short-lived. In 2021, specific institutional conditions were established, and state and regional management initiatives were implemented, significantly impacting the population’s economic activity. As a result, the number of individuals engaging in entrepreneurial activities (third-level economic activity) increased. A regulatory framework was established (securing new institutional conditions) to promote economic activity in the form of self-employment (second-level economic activity), contributing to a positive trend in self-employment in Tuva. From 2012 to 2022, there was a gradual decrease in the proportion of people employed in traditional economic sectors for Tuvan residents. In 2022, the number of people employed in agriculture, forestry, hunting, fishing, and fish farming increased. However, as the primary economic strategy of the population in Tuva is adaptive, it is too early to determine whether the positive trends will continue if the intensity of state and regional support for entrepreneurship and self-employment decreases.